Persepsi Siswa SMA/SMK di Kota Pasuruan terhadap Sistem Kontrak Kerja dan Implikasinya Bagi Pemula di Dunia Kerja - Muhammad Ridwan; Yulia Nor Frasisska; Rima Melati; Firza Agung Prakoso (Pajak dan Manajemen Keuangan, 2024)
This study explores the views of high school/vocational school students in Pasuruan City regarding the employment contract system and its impact on their readiness to enter the world of work. With a quantitative approach and survey method, this study involved 54 grade XI students who were selected using the purposive sampling technique. Data collection was carried out through a closed questionnaire, while data analysis used simple linear regression. The results of the analysis showed that students' perception significantly affected their readiness to work, with a regression coefficient of 0.748 and a significance value of 0.000 (p < 0.05). An R Square value of 0.500 indicates that 50% of the variation in job readiness can be explained by students' perception of the employment contract system. The regression assumption test showed that the data met the requirements of normality, homoscedasticity, and no autocorrelation was found. The results of this study highlight the importance of providing a deeper understanding of the employment contract system to increase students' readiness to face the world of work.